Association of Locomotor Activity During Sleep Deprivation Treatment With Response - Foo, Jerome Clifford; Sirignano, Lea; Trautmann, Nina; Kim, Jinhyuk; Witt, Stephanie H.; Streit, Fabian; Frank, Josef; Zillich, Lea; Meyer-Lindenberg, Andreas; Ebner-Priemer, Ulrich; Schilling, Claudia; Schredl, Michael; et al. (Frontiers in Psychiatry, 2020)
Disrupted circadian rhythms and sleep patterns are frequently observed features of psychiatric disorders, and especially mood disorders. Sleep deprivation treatment (SD) exerts rapid but transient antidepressant effects in depressed patients and has gained recognition as a model to study quick-acting antidepressant effects. It is of interest how locomotor activity patterns during SD might be associated with and potentially predict treatment response. The present study is an analysis of locomotor activity data, previously collected over a 24 hour period, to examine the night of SD (Trautmann et al. 2018) as mood disorder patients suffering from a depressive episode (n = 78; after exclusions n = 59) underwent SD. In this exploratory analysis, the associations between response to SD, locomotor activity and subjective mood during the 24 hour period of SD were explored. Higher levels of activity overall were observed in non-responders (n = 18); in particular, non-responders moved more during the evening of SD until midnight and remained high thereafter. In contrast, activity in responders (n = 41) decreased during the evening and increased in the morning. Subjective mood was not found to be associated with locomotor activity. The window of data available in this analysis being limited, additional data from before and after the intervention are required to fully characterize the results observed. The present results hint at the possible utility of locomotor activity as a predictor and early indicator of treatment response, and suggest that the relationship between SD and locomotor activity patterns should be further investigated.